2012
DOI: 10.15376/biores.7.4.5167-5180
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillated Cellulose as Paper Additive in Eucalyptus Pulps

Abstract: In this work, the physical and mechanical properties of bleached Eucalyptus pulp reinforced with nanofibrillated cellulose (NFC) are compared with those of traditional beaten pulp used in the making of writing/printing and offset printing papers. For this purpose, three different types of hardwood slurries were prepared: beaten pulps, unbeaten pulps reinforced with NFC, and slightly beaten pulps also reinforced with NFC. Physical and mechanical tests were performed on handsheets from these different slurries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
2
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(140 citation statements)
references
References 16 publications
10
120
2
8
Order By: Relevance
“…In addition, further refining, besides consuming more energy, could cause structural damages that limit the performance of the fibres (Hubbe 2014;Gharehkhani et al 2015). This undesired behaviour as pulp is further refined has been also observed for other pulps, regardless of the origin of the raw material and the pulping process (González et al 2012(González et al , 2013Delgado-Aguilar et al 2015).…”
Section: Mechanical Properties Of Rapeseed Tmp and Recycled Fluting Pmentioning
confidence: 87%
“…In addition, further refining, besides consuming more energy, could cause structural damages that limit the performance of the fibres (Hubbe 2014;Gharehkhani et al 2015). This undesired behaviour as pulp is further refined has been also observed for other pulps, regardless of the origin of the raw material and the pulping process (González et al 2012(González et al , 2013Delgado-Aguilar et al 2015).…”
Section: Mechanical Properties Of Rapeseed Tmp and Recycled Fluting Pmentioning
confidence: 87%
“…External fibrillation was clearly seen on the surface of soda-AQ durian rind beaten pulps (Figure 4). These fibrils increased the surface area of fibre (allowing better interaction between fibres), as well as increased hydrogen bonding and filled empty spaces (González et al 2012). Beating increases the surface charge and specific surface area, thus enhancing paper fibre-to-fibre bonding (Bhardwaj et al 2007, Banavath et al 2011, González et al 2012.…”
Section: Image Analysismentioning
confidence: 99%
“…These fibrils increased the surface area of fibre (allowing better interaction between fibres), as well as increased hydrogen bonding and filled empty spaces (González et al 2012). Beating increases the surface charge and specific surface area, thus enhancing paper fibre-to-fibre bonding (Bhardwaj et al 2007, Banavath et al 2011, González et al 2012. Masrol et al (2015a) reported that fibre arrangement and bonding of durian rind pulp Values are means ± standard deviations produced by chemi-mechanical pulping process were not uniform, not straight and had some kinks and crimps compared with soda-AQ pulp.…”
Section: Image Analysismentioning
confidence: 99%
“…Opacity is a function of paper thickness, amount of fi ller(s), pulp brightness, and beating degree. Beating makes the paper denser, but excessive beating results in low opacity (GONZÁLES et al, 2012). The scattering coeffi cient is a measure of the ability of Potential of bleached elephant grass soda pulp for production of printing and writing paper grade…”
Section: Opacity and Scattering Coeffi Cientmentioning
confidence: 99%